2003
DOI: 10.1046/j.1440-1746.2003.03044.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous dysfunction in patients with liver cirrhosis using 123I‐metaiodobenzylguanidine myocardial scintigraphy and spectrum analysis of heart‐rate variability

Abstract: The present results indicate that autonomic abnormalities appear early in LC, and that these abnormalities can be detected by MIBG myocardial scintigraphy and analysis of heart-rate variability. We consider these methods to be clinically useful for the quantitative detection of hyperdynamic circulation of liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…These results are in agreement with previous observations in similar patient populations (21,24). Several variables pertaining to a sympatho-vagal imbalance correlated significantly with H/M ratios of mIBG uptake as obtained by mIBG scintigraphy and suggest that decreased HRV is also reflected by the abnormal mIBG uptake in the heart in contrast to what has previously been reported (17). In analogy with the present findings, we and others have previously found altered response to head-up tilt in cirrhotic patients, suggesting impaired cardiovascular regulation and myocardial contractility (20,37).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with previous observations in similar patient populations (21,24). Several variables pertaining to a sympatho-vagal imbalance correlated significantly with H/M ratios of mIBG uptake as obtained by mIBG scintigraphy and suggest that decreased HRV is also reflected by the abnormal mIBG uptake in the heart in contrast to what has previously been reported (17). In analogy with the present findings, we and others have previously found altered response to head-up tilt in cirrhotic patients, suggesting impaired cardiovascular regulation and myocardial contractility (20,37).…”
Section: Discussionsupporting
confidence: 92%
“…In that study, the authors did not find significant changes in early and late H/M ratio but significantly higher WOR in cirrhotic patients correlating with plasma levels of noradrenaline, albumin, coagulation factor 2, 7, and 10, and Child score. The authors conclude that autonomic abnormalities even in early cirrhosis can be detected by mIBG myocardial scintigraphy (17). In our study, we extended this approach to a group of cirrhotic patients and controls well characterized with respect to hemodynamics, pulmonary function, cardiac and autonomic function, and neurohumoral abnormalities.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Mani et al [13] documented significant reduction of SDNN, LH and HF in cirrhotic subjects (n = 80) with encephalopathy compared to healthy volunteers (n = 11); significant differences were not found for LH/HF ratio. [6] reported that HRV abnormalities appear in early stages of liver cirrhosis and depend on changes of norepinephrine level. Circadian variation of HRV parameters is reported by some authors.…”
Section: Discussionmentioning
confidence: 99%
“…Haemodynamic, electric and regulatory mechanisms are affected. There is evidence on development of autonomic nervous system disorders resulting in sympathetic-parasympathetic imbalance, disturbed autoregulation of brain flow and peripheral vessel reactivity [5,6]. A non-invasive tool for evaluation of autonomic nervous system function in cardiovascular diseases is estimation of parameters of heart rate variability (HRV).…”
Section: Introductionmentioning
confidence: 99%